Pengaruh Work Life Balance dan Flexible Working Arrangement Terhadap Kepuasan Kerja dengan Employee Engagement dan Resilience Employee sebagai Variabel Moderasi (Studi Pada Pekerja Generasi Z di Kota Bandung) - Muhamad Iqbal Ramadhan; Neuneung Ratna Hayati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study analyze the effect of work-life balance and flexible working arrangements on job satisfaction among Gen-Z workers in Bandung, with employee engagement and employee resilience as moderating variables. Using a quantitative approach, 400 Generation Z workers (born 1997–2012) employed for a minimum of six months were surveyed. Data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The research show that both work-life balance and flexible working arrangements significantly increase job satisfaction. Employee engagement negatively moderates the work-life balance–job satisfaction relationship but positively moderates the flexible working arrangements–job satisfaction relationship. Employee resilience does not significantly moderate either relationship. These findings highlight the importance of organizational policies supporting work-life balance and workplace flexibility, coupled with strengthened employee emotional engagement, in enhancing job satisfaction for Gen-Z workers.